Study of anticonvulsant properties of 1,2,4-triazole derivatives and prospects for their use in pharmacy - N. M. Borysenko; V. V. Parchenko; I. V. Bushuieva; O. K. Yerenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2025)
Anticonvulsant drugs (antiepileptic drugs) are a group of medications used to treat epilepsy and to control other disorders associated with seizures or convulsive episodes. The choice of a particular drug depends on the type of seizure, the patient’s age, comorbidities, and possible side effects. Treatment with these drugs requires constant medical monitoring to achieve optimal impact and to minimize risks. Therefore, solving the problem of creating new original medicines with minimal adverse effects remains an urgent task, with theoretical and practical justification.